2012
DOI: 10.1038/hr.2012.146
|View full text |Cite
|
Sign up to set email alerts
|

Intake of high sucrose during pregnancy altered large-conductance Ca2+-activated K+ channels and vessel tone in offspring’s mesenteric arteries

Abstract: Antenatal malnutrition could be linked to hypertension and vascular diseases in fetal origins. This study determined the influence of maternal intake of high sucrose (HS) during pregnancy on vessel tone, intracellular Ca(2+) ([Ca(2+)](i)), K(+) channels, especially large-conductance Ca(2+)-activated K(+) channels (BK), in mesenteric arteries in the offspring rats exposed to prenatal HS. Vessel tension and [Ca(2+)](i) induced by angiotensin II were higher in the small mesenteric arteries of the HS offspring. In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 38 publications
0
20
0
Order By: Relevance
“…Contrarily, the reduction in BKCa channel activity due to channel dysfunction in vascular smooth cells can blunt the negative regulation of vessel tone [33,37,38]. Recent studies have shown that BKCa channels have a pathophysiological role in the development of adverse cardiovascular outcomes following exposure to prenatal insults [12,16]. Our vasoconstriction and electrophysiological data suggested that AII-induced vasoconstrictions in HS offspring’s MCA were partially attributed to the reduced BKCa channel activity, which could be explained in either of two ways: (1) as shown in whole-cell K + currents data, the baseline of whole-cell K + currents as well as the decreased K + currents by the BKCa channels inhibitor were reduced in HS group, indicating that BKCa currents in HS offspring’s MCA were less than that in the control.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Contrarily, the reduction in BKCa channel activity due to channel dysfunction in vascular smooth cells can blunt the negative regulation of vessel tone [33,37,38]. Recent studies have shown that BKCa channels have a pathophysiological role in the development of adverse cardiovascular outcomes following exposure to prenatal insults [12,16]. Our vasoconstriction and electrophysiological data suggested that AII-induced vasoconstrictions in HS offspring’s MCA were partially attributed to the reduced BKCa channel activity, which could be explained in either of two ways: (1) as shown in whole-cell K + currents data, the baseline of whole-cell K + currents as well as the decreased K + currents by the BKCa channels inhibitor were reduced in HS group, indicating that BKCa currents in HS offspring’s MCA were less than that in the control.…”
Section: Discussionmentioning
confidence: 99%
“…Rings of MCA were carefully prepared, and mounted in a multimyograph system (Danish Myo Technology, Midtjylland, Denmark) for recording of isometric tension [3,12]. The vessel rings were given an initial tension and were equilibrated for 60 min.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…At gestational day (GD) 21, rats were anesthetized with a mixture of ketamine (75 mg/kg) and xylazine (10 mg/kg; Hengrui Medicine, Jiangsu, China) intraperitoneally [18] and at GD 26, rabbits were anesthetized intravenously with ketamine (30 mg/kg) [19] through an ear vein followed with uterine-incision delivery. Umbilical cords were collected and kept in Ca 2+ -free physiological salt solution.…”
Section: Methodsmentioning
confidence: 99%